3(c+7)-6c=4

Simple and best practice solution for 3(c+7)-6c=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(c+7)-6c=4 equation:


Simplifying
3(c + 7) + -6c = 4

Reorder the terms:
3(7 + c) + -6c = 4
(7 * 3 + c * 3) + -6c = 4
(21 + 3c) + -6c = 4

Combine like terms: 3c + -6c = -3c
21 + -3c = 4

Solving
21 + -3c = 4

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-21' to each side of the equation.
21 + -21 + -3c = 4 + -21

Combine like terms: 21 + -21 = 0
0 + -3c = 4 + -21
-3c = 4 + -21

Combine like terms: 4 + -21 = -17
-3c = -17

Divide each side by '-3'.
c = 5.666666667

Simplifying
c = 5.666666667

See similar equations:

| 4cos(2x-60)=2 | | 24x^2+3x-2=0 | | 2x+10-6x= | | 2a^2-pa+3=0 | | 7x(1-5)+2=6 | | 4x-6=-3x | | D+7=3d-2 | | 18-9+r^2=0 | | 8+6x=11x+12 | | log(51x)+log(2x)=log(3x)+log(1) | | (14x^2+7x)9x^2= | | 4q=12-2q | | 15x-7=5(3x-1) | | 10x-5=-6x-7 | | ln(4x)+2ln(x)=ln(3x)+ln(1) | | 3(1.25-2.48x)=8.15x+5.86 | | x+4y-z=-4 | | 8x-y+4z=46 | | 1.59x+3.01=10.9x+1.29 | | 4(x-5)=4s-20 | | 1.50x+5=8.25 | | 2u+4(u-3)=30 | | -8+2x-9+3x-10=21 | | .50x+5=8.25 | | 12p+3q= | | 6x+5=10x+5-4x | | 8x+3=12+11x | | 18=8 | | 6+4=4w+11 | | 8+4=4+10 | | 2x-(x+3)=0 | | 30+2x=27+4x |

Equations solver categories